PROVISION OF GREEN PRACTICES AMONGST HOMESTAY OPERATORS IN KELANTAN - Nur Farihin Abd Hadi Khan; Roslizawati Che Aziz; Nik Madeeha Nik Mohd Munir; Azlinda Shazneem Md. Shuaib; Nurul Hasliana Hamsani (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This paper reports on the initial findings on environmental decision-making in the context of Malaysian small service accommodation called Homestay. The study was conducted in Kelantan and involved registered Homestay operators whereby the list was obtained from the Ministry of Tourism and Cultural, Malaysia. In order to determine the main activity of green practices by the Homestay operators in Kelantan, 108 questionnaires have been distributed through the implementation of purposive sampling method. Descriptive analysis was applied and it can be concluded that there is certain application of green practices in these small service accommodations.